Penggunaan Jalur Pejalan Kaki di Koridor Jalan Pahlawan dan Jalan Pemuda Kota Semarang oleh Masyarakat Difabel - Pratama, Pradipta (Magister Pembangunan Wilayah dan Kota,Undip, 2016)
Pahlawan streets and Pemuda streets has recently experienced significant improvements in improving the quality of public space in particular pedestrian ways. Significant improvements were addressed by the government of Semarang that all segments of society could use it more comfortable and safe, but in reality both pedestrian ways in the two corridors is still rarely seen used by people with disabilities. Referring to the problems it is the thought that research is needed to evaluate the use of pedestrian ways on Pahlawan streets and Pemuda streets for people with disabilities. The purpose of this study was to evaluate the use of pedestrian ways for people with disabilities as well as obtain the factors that cause minimal numbers people with disabilities who access the pedestrian ways. Research targets are to be achieved by identifying the feasibility s tudy of literature and the public perception of disability. The research method uses deductive research methods with qualitative descriptive analysis techniques. This technique is done by commenting on the feasibility of the elements contained in the pedestrian ways based on the literature and the public perception of disability. Based on a literature review that refers to problems in the field of research obtained variables which are divided into two focus the observation were variables pedestrian ways and variables public perception disabilities. For people with disabilities who selected were the physically disabled, visually impaired, hearing impaiired and ederly with perception measurement include comfort, convenience, safety, achievement, usability, sensitivity and independence. Based on the results of the analysis it is known that both the pedestrian ways on Pahlawan streets and Pemuda streets can not be said to be feasible for handicapped due to the lack of quality of both the pedestrian ways. It is also known that there are external and internal factors that dominate cause the minimum number of people with disabilities ranging from pedestrian ways conditions, their own motivation or desire, age and availability of transportation. Under these conditions, the improvements in both the pedestrian ways is necessary to improve the quality of its use for people with disabilities.